Spatial variation of coda wave attenuation in the Southern Indian Shield and its implications - C. SINGH; S.K. BASHA; M. SHEKAR; R.K. CHADHA (Geologica Acta, 2012)
During the recent past the Indian peninsular shield has experienced six damaging earthquakes of M 5.4-7.7 and compelled to readdress our understanding of the seismic attenuation characteristics for better evaluation of the seismic hazards in the so-called stable shield. We have performed the seismic attenuation study using coda waves of the broadband network from 1995 to 2009 for the shield region. About 400 local earthquakes M 2.5-4.0 within an epicentral distance of 250km are used in this study. The broadband seismic stations established are in different geological provinces, such as the Archaean Dharwar craton, the southern granulite terrain, the Proterozoic Cuddapah basin, the Godavari graben, the Cretaceous-Eocene Deccan volcanic province and in the Cambay basin. This allows us to understand the fluctuation of Q0 in terms of spatial variations in the geologic and tectonic provinces. The results reflect a ubiquitous observation of frequency dependence of Qc in the different geologic provinces. The rift basins exhibit lower Q0, which suggests higher attenuation due to a more heterogeneous structure. Higher Q0 in the western Dharwar craton infers lower attenuation. Similarly the Deccan volcanic province is characterized by significantly higher Q0. The results show a good correlation with the observed heat flow. The study fills an important gap in knowledge about the Q factor as well as of crustal attenuation conditions in the whole southern peninsular shield of India.